Wheat (Triticum spp) roots influenced by crop residue and phosphorus under maize (Zea mays)-wheat system - SHARMA, V K; MEENA, M C; DWIVEDI, B S; KUMAR, SARVENDRA; CHOBHE, KAPIL A; DEY, ABIR; ANIL, AJIN S; T, MOHANKUMAR K (The Indian Journal of Agricultural Sciences, 2021)
A field experiment was initiated with maize (Zea mays L.)-wheat (Triricum spp.) cropping system in the year 2013to assess the impact of crop-residue retention (CCR) and phosphorus fertilization on root growth, growth parameters and nutrient content of wheat at ICAR-Indian Agricultural Research Institute Research Farm, New Delhi. Treatments of main-plot were of different CRR and that of subplot were of different P fertilizer management accounting for 20 treatments combinations. For the present study, collected samples were analyzed during 2014–15 and 2015–16 using appropriate methods. Results indicated that mean root-weight densityof wheat at 40 and 75 days after sowing (DAS) was significantly increased from 0.64 (control) to 0.84 mg/cm3 and 2.19 (control) to 2.82 mg/cm3 with 50% cropresidue retention (CRR), respectively. Similarly, the root-growth rate of wheat was also affected significantly due to CRR under different treatments over control. The treatment 50% RDP + PSB amd AM significantly enhanced dry root weight density (0.91 mg/cm3 at 40 and 2.82 mg/cm3 at 75 DAS of wheat with root-growth rate of 48.5 μg/cm3/day). Moreover, significant highest root-growth rate was noticed (49.2μg/cm3/day) under 150% RDP treatment which was statistically similar to 50% RDP + PSB and AM treatment. Significant highest P content in wheat at different stages as well as in grain was recorded with 50% CRR along with 50% RDP + PSB and AM treatment combination. Application of 50% RDP+PSB and AM in combination with 50% CR was found most beneficial in terms of improving root-growth rate, root-weight density, growth attributes and P content in wheat at different stages as well as in grain.